Vom Trauma zum bedeutungsvollen Ersterlebnis: Über die Entstehungsbedingungen von Person und Personalität aus Sicht der medizinischen und der Philosophischen Anthropologie - Schmidt, Christian (Verlag Karl Alber, 2024)
Based on considerations by the anthropologically oriented psychiatrist Erwin Straus, this book explores the conditions which are present when people experience certain events as significant. In addition, it discusses in detail how personhood emerges in humans and to what extent this depends on the successful integration of meaningful first experiences. The underlying concept of the person is an independent attempt to synthesise the four concepts developed by Erwin Straus, Viktor Emil von Gebsattel, Helmuth Plessner and Max Scheler. The author works in a leading medical position at Klinikum Schloss Lütgenhof, an acute clinic for person-centered medicine, integrated psychosomatics, internal medicine and psychotherapy.